2016
DOI: 10.1007/s13320-016-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis of NO2 Gas Sensor Based on Carbon Nanotubes

Abstract: Two types of carbon nanotubes [single walled nanotubes (SWCNTs) and multi walled carbon nanotubes (MWCNTs)] are deposited on porous silicon by the drop casting technique. Upon exposure to test gas mixing ratio 3% NO 2 , the sensitivity response results show that the SWCNTs' sensitivity reaches to 79.8%, where MWCNTs' is 59.6%. The study shows that sensitivity response of the films increases with an increase in the operating temperature up to 200• C and 150℃ for MWCNTs and SWCNTs. The response and recovery time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…At the rst time the digital multi-meter records the biasing current of air ow, aer that the testing gas is switched on, and aer several seconds the current has low variation, and then the test gas is switched off to record the recovery time. 46 The testing gases used to study the sensing behavior of compounds 4i and 5i are a reducing gas (NH 3 ) and oxidative gas (NO 2 ).…”
Section: Sensor Testingmentioning
confidence: 99%
“…At the rst time the digital multi-meter records the biasing current of air ow, aer that the testing gas is switched on, and aer several seconds the current has low variation, and then the test gas is switched off to record the recovery time. 46 The testing gases used to study the sensing behavior of compounds 4i and 5i are a reducing gas (NH 3 ) and oxidative gas (NO 2 ).…”
Section: Sensor Testingmentioning
confidence: 99%
“…Multiwalled carbon nanotubes (MCNTs) have also been used to develop NO2 gas sensors which are capable of measuring low concentration going down to 0.1 ppm [146]. Another work has reported the detection of NO 2 using a combination of SWCNTs and MWCNTs on porous silicon wafers which was done at different temperatures [147]. Their results indicated that the equal sensitivity for the two types of CNTs was achieved with higher temperatures for the SWCNTs as compared to the MWCNTs.…”
Section: Carbon Nanotubes In Gasmentioning
confidence: 99%
“…Among different CNTs, SWCNT showed better performances in terms of sensitivity to gas exposure with respect to the MWCNTs and this is mainly due to a lower percentage of semiconducting nanotubes that can be modulated by the target gas molecules, whereas the multi-wall structures show, in general, shorter response time and usually work at a lower temperature [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%